Effective Design of Tailings Pond Size for the Management of Iron Ore Tailings in Indian Context (ABSTRACT PAGE) - Mrinal K. Ghose; P. K. Sen (International Mineral Processing Congress, 2003)
Tailing slurry is usually abrasive and possesses high viscosity. This paper examines the existing iron ore beneficiation process and focuses on some of the key environmental issues related to the disposal of tailings. It identifies that almost 32% of the iron ore extracted ends up as tailings and they are usually disposed in slurry form in tailing ponds. By the year 2000, 27 Mt of iron ore tailings were generated in India, which has become one of the biggest waste handling problems to the industry. Characteristics of the tailings vary widely. So the physical nature of tailings cannot be considered separately in isolation without considering the mill effluent from the beneficiation plant. In the present investigation, studies were carried out in three iron ore mines in India to evaluate the characteristics of tailings from the beneficiation plant. The tailing samples were collected from different locations during a time period of one year and analyzed. The results will be discussed and the characteristics of the tailings have been evaluated. The disposal system of tailings at the three mines was evaluated. The research on the settling characteristics of tailings indicates that the area provided in the existing tailing ponds in India is much more than that of the experimental results. This paper concludes that sedimentation tests are essential to design appropriate tailings pond with respect to size. In the proposed scheme it is suggested that an additional unit process, i.e. sedimentation tank be added to the process before the disposal of tailings to the tailing pond.